ZnO single microwire homojunction light emitting diode grown by electric field assisted chemical vapor deposition. Issue 18 (14th May 2015) - Feng, Qiu-Ju; Liang, Hong-Wei; Mei, Yi-Ying; Liu, Jia-Yuan; Ling, C. C.; Tao, Peng-Cheng; Pan, De-Zhu; Yang, Yu-Qi
<x xml:space="preserve">Abstract</x> A single large-scale ZnO microwire (MW) homojunction LED is fabricated by an electric field assisted chemical vapor deposition method.